UJI KUALITAS AIR MINUM ISI ULANG DI KOTA BATUSANGKAR - SARI, MAYA (Sainstek : Jurnal Sains dan Teknologi, 2013)
The purpose of this study was to test the quality of drinking water in the district refill Batusanggkar The Limo. Because of the tendency found in water use rechargeable (AMIU) by society, especially in urban areas, especially cities Batusanggkar increasing. However, the quality still needs to be studied in order to secure the quality of drinking water that directly affect public health, the course of a study of drinking water quality testing that has been done in District Batusangkar The limo showed that 9.1% of drinking water depots produce drinking water quality does not meet the requirements biological parameters (microbiological) that has been set by the government through Permenkes. 492 of 2010 on drinking water quality requirements, while for Physical parameters (temperature) and chemical parameters (pH) has met the requirements of the government.Key words: drinking water, Escherichia coli , temperature, ph